BASALT FIBER CONCRETE PROPERTIES AND APPLICATIONS - Abdullaev Ibrohim Numanovich; Rakhimov Rasuljon Ravshanbek o'g'li (Journals Park Publishing, 2022)
Technical characteristics of basalt fiber are shown: Concrete made using basalt fiber has its own characteristics, which differ significantly from other fibers. Areas of application of basalt fiber are given.
Keywords: Basalt fiber, concrete mix, basalt fiber reinforced concrete, cement stone.